Scooby-Doo! and the movie monsters [videorecording (DVD)]. (Warner Home Video, 2018)
"Never Ape an Ape Man": Daphne's uncle is directing a horror movie about an ape man; but a real ape man shows up and wreaks havoc on the set. "That's Monstertainment": Horror host and demon chest escapee Zomba magically transports Scooby and the gang into the film "The Son of the Bride of the Ghost of Frankenstein."